DETERMINAN DETEKSI KECURANGAN LAPORAN KEUANGAN - Siti Rohmah; Erni Setawati; Pantas P. Pardede; Mutiara Rahman (Jurnal GeoEkonomi, 2024)
According to CNBC Indonesia 2023, financial reports include information on a company's financial situation as well as the growing development of the capital market. A number of manufacturing enterprises operating in the consumer goods industry sector, such as PT Kimia Farma Tbk (KAEF), PT. Indofarma Tbk (INAF), and PT Tiga Pilar Sejahtera Food Tbk (AISA), are involved in financial report fraud. We aim to investigate the effects of financial stability, financial targets, external pressure, and supervisory ineffectiveness—a perspective in fraud theory that has three conditions—on the quantitative methods—that is, methods that use numerical research data—used to detect financial statement fraud. This research is a manufacturing business registered on that is part of the consumer products industrial category. According to the study's findings, financial stability alone has a limited impact on the identification of financial statement fraud, whereas external pressure, financial targets, supervisory inefficiency, and financial stability all have no influence on the detection of financial report fraud.